PEMANFAATAN MEDIA BROSUR DALAM BUDIDAYA PADI SAWAH DI DESA PANGKURI KECAMATAN RAROWATU KABUPATEN BOMBANA - Muh. Ramadan Gafar; Ima Astuty Wunawarsih; Salahuddin Salahuddin; Arfiani Arfiani (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2025)
The objective of this study is to ascertain the utilization of brochures in the context of rice cultivation in Pangkuri Village, Rarowatu District, Bombana Regency. The population of this study consists of farmers residing in Pangkuri Village, with a total of 284 farmers included in the analysis. The sample size was determined using the Slovin formula with a 15% error margin, resulting in a sample size of 38 individuals. The data was collected through a combination of survey techniques, documentation, and interviews, with the use of questionnaires. The research variable is the utilization of brochures in rice cultivation. The researchers employed descriptive analysis, utilizing class interval formulas, to address the research objectives. The results of the study indicate that the use of brochures in rice cultivation in Pangkuri Village is categorized as good, both as a source of information, a learning tool, and a source of inspiration for innovation, with the majority of farmers actively utilizing brochures to enhance their knowledge, skills, and agricultural productivity. Brochures have proven to be an effective medium for conveying technical information concisely and visually, ranging from cultivation techniques to environmental management, and encouraging farmers to adopt more efficient and sustainable agricultural practices. The role of brochures in various dimensions of farmer learning, from information dissemination, facilitating self-directed learning, to encouraging local innovation in agricultural practices. Simple printed media like brochures still hold high relevance in the digital age, especially in rural contexts with limited access to technology, and can serve as an effective communication strategy in community-based agricultural extension programs.